IMPLEMENTASI PEMBINAAN, PEMANTAUAN DAN EVALUASI KINERJA PELAKSANA PENEMPATAN TENAGA KERJA INDONESIA SWASTA (PPTKIS) OLEH BALAI PELAYANAN PENEMPATAN DAN PERLINDUNGAN TENAGA KERJA INDONESIA (BP3TKI) PONTIANAK - Raisa Mayesti E.01108073 (PublikA, Jurnal Ilmu Administrasi Negara, 2013)
Topic of this research was chosen because of there were so many problematic cases that experienced by people working aboard legally and illegally, even though the government has set program of the location and protection of indonesian workers aboard. The purpose of this research is to know the process of implementation guidance, monitoring and evaluation of the executive’s performance of indonesian workers location by the center for location services and indonesian workers protection at Pontianak in implementing location and protection program indonesian workers aboard. The method of this research used qualitative method. The result of this research is the training and monitoring function to  executive’s private of indonesian workers location didn’t do optimal yet by the center for location services and indonesian workers protection at Pontianak. The evaluation result of the center for location services and indonesian workers protection at Pontianak to executive’s private of indonesian workers location was difficult to find the candidates of indonesian workers who want to work aboard. Except that, it was still found executive’s private of indonesian workers location who work outside of the procedure. This led too many problems involving indonesian workers location. So that’s why it takes cooperative and commitment by all participants involved for the achievement of the objective program. Key Word : Manpower Location Training, Manpower Location Monitoring, Performance Evaluation, Employees’ Cooperative, Employees’ Commitment.